Heuristic-based optimisation approach: cost-effective school transportation. Issue 4 (2nd July 2022) - Dragan, Dejan; Keshavarzsaleh, Abolfazl; Popović, Vlado; Jereb, Borut; Intihar, Marko
Abstract : The provision of optimised routing solutions is a priority to generate maximum decreases in the cost of school transport. The aim of this study was to achieve a reduction in existing costs while processing the fare-free transportation of eligible pupil commuters (PCs). The optimisation problem comprised the minimisation of vehicle costs and the total travel time for all pupils. To solve this problem, a heuristic algorithm was developed based on route planning dependent on changes in schools' starting times so that vehicles can visit a greater number of schools within one route. The algorithm was applied to a municipality in the EU region and the optimised system has been successfully running for 5 years. This study differs from others as it deploys a two-mechanism procedure: the identification of eligible PCs prior to assigning them to bus stops and determining the optimal assignment of school start/finish times for selected schools simultaneously with optimal driving routes and vehicle fleet. After application of the optimisation to the municipality, the total daily mileage of all vehicles was almost 300 km less than the previous un-optimised situation, while the total number of vehicles was reduced by almost 50%.